Recombinant Escherichia coli Strain with Enhanced Production of Vibrio cholerae Neuraminidase - E. V. Monakhova; G. V. Demidova; R. V. Pisanov; O. V. Duvanova; B. N. Mishan’kin (Проблемы особо опасных инфекций, 2019)
Objective of this work was cloning of the Vibrio cholerae nanH gene as part of a plasmid vector, providing expression of foreign genes under the control of T5 promoter, and construction of a E. coli strain – producer of V. cholerae recombinant neuraminidase.Materials and methods. V. cholerae о1 strain served as a DNA donor, pQE30 – as a vector plasmid. The gene was PCR-amplifi ed, the cloning was carried out by means of conventional methods, performance of recombinants and localization of the required protein was determined based on the results of electrophoresis of cell lysates. Neuraminidase activity was identifi ed by fl uorescence in ultraviolet light after incubation with specifi c substrate (4-methylumbelliferyl-N-acetylneuraminic acid).Results and discussion. Recombinant plasmid pNanH, containing the cloned gene nanH V. cholerae, has been constructed. The gene is inserted into BamHI-PstI sites of the polylinker of pQE30. Expression of the cloned gene in the producer strain E. coli JM103pNanH occurs under the control of T5 promoter after isopropyl-1-thio-β-D-galactopyranoside (IPTG) induction. The strain shows neuraminidase activity. The recombinant NanH protein is accumulated in the producer’s cells in two forms. The fi rst form, with molecular mass (MM) of 89.5 kDa, is an unprocessed protein with the hexahistidine block (6His-tag) at its N-terminus, it is located in inclusion bodies. Its percentage is 5.6–6.6 % of the total cell proteins. The second one, with MM of 83 kDa, is found in the periplasmic space and corresponds to the mature NanH, its percentage being 3.4–3.8 %. The total percentage of both forms is 9–10 % of total cell proteins, which allows to consider the strain E. coli JM103pNanH to be a super-producer of the required protein. The strain may be used for purifi cation of NanH preparations for construction of specifi c diagnostic, therapeutic and pharmaceutical preparations as well as for investigation of the protein as a virulence/persistence factor of the pathogen.